Metabolism of Natriuretic peptides and impact on insulin resistance and fat mass in healthy subjects - Prickett, Timothy C.R.; Lewis, Lynley K.; Pearson, John F.; Espiner, Eric A. (Clinical biochemistry, 2025)
•Reduced natriuretic peptides (NP) associate with insulin resistance (IR) in obesity.•Whether due to higher clearance or altered molecular forms is unknown.•In a community study we find clearance does not account for lower levels.•Bioinactive NTproANP and NTproBNP outperform bioactive ANP and BNP in predicting IR.•Genetic factors not clearance or altered NP forms underlie the link of NP with IR. Natriuretic peptides (NP) have important roles in regulating fat balance and metabolic health. Reduced concentrations of ANP and BNP in plasma are associated with increased insulin resistance in obesity. Whether this is due to increased clearance or reduced bioactivity of immunoreactive NP forms is unclear. These questions were addressed in a community study of mildly obese subjects at middle age. The ratio of amino-terminal (NT) pro-NP to bioactive C-terminal NP was used as a putative index of the clearance of bioactive forms. Lower ratios of amino-terminal pro-NP to bioactive C-terminal NP were associated with increased insulin resistance. In linear regression models, NT-proANP and NT-proBNP outperformed ANP and BNP in predicting insulin resistance. Pro-NP glycosylation, which can impair NP and NT-proNP production in obesity, does not account for the diminished impact of ANP or BNP. Plasma concentrations of osteocrin, which competes for the NP clearance receptor (NPR-C) and potentially enhances NP bioactivity, was not associated with NPs, but did positively predict insulin resistance in females. We find no evidence that increased clearance/degradation of NPs contributes to insulin resistance. Among the nine NP variants assessed, only NT-proANP and NT-proBNP independently predicted insulin resistance in both sexes. The impact of CNP on fat mass or insulin resistance was minor but significant in females. Lower concentrations of immunoreactive plasma ANP and BNP remains unexplained and requires closer study.